Immunosuppression in Uterus Transplantation: Experience From the Dallas Uterus Transplant Study. Issue 3 (21st February 2023) - Wilson, Nicole K.; Schulz, Philipp; Wall, Anji; Parrott, Megan; Testa, Giuliano; Johannesson, Liza; Sam, Teena
Abstract : Background: Uterus transplantation is a temporary transplant allowing women with absolute uterine factor infertility to experience pregnancy and childbirth. The degree of immunosuppression (IS) required to prevent rejection while minimizing toxicity to the recipient and fetus remains an area of investigation. Methods: In this article, we describe immunosuppressive therapy, rejection episodes, infections, and adverse events in 14 uterus transplant recipients. Induction consisted of antithymocyte globulin and methylprednisolone. Ten recipients (71%) received no steroids postoperatively, and 4 (29%) had steroids tapered off at 42 d. All received oral tacrolimus, either immediate release (n = 2, 14%) or extended release (n = 12, 86%). Mycophenolate was used in 4 cases (29%), de novo azathioprine in 9 (64%), and de novo everolimus in 1 (7%). Results: Sixteen clinically silent, treatment-responsive rejection episodes occurred in 10 recipients. Five recipients (36%) experienced acute kidney injury. In 3 recipients, IS was discontinued due to renal dysfunction. Eleven infection episodes were noted in 7 recipients. No babies had congenital abnormalities. Conclusions: Our experience demonstrates that safe IS regimens can be used for uterus transplant recipients before and during pregnancy.